GERAKAN MAHASISWA BERBAGI KEPEDULIAN MELALUI PENYALURAN BANTUAN SEMBAKO DAN PAKAIAN LAYAK PAKAI DI DESA BREBEK SIDOARJO - Afif Amrullah; Eka Julia Indah Nur safitri; arif rachman putra; yeni vitrianingsih; reva zhori fahdhani (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Socio-economic disparities and soaring living costs make it difficult for low-income communities to meet their basic needs. As a solution, the Student Movement for Sharing Care organised a Community Service (PkM) initiative through the distribution of basic foodstuffs and suitable clothing. This programme aims to alleviate the burden on vulnerable groups whilst fostering empathy and social responsibility among students. The method employed is the Asset-Based Community Development (ABCD) approach, which optimises local assets, social capital, and active participation from the planning stage through to evaluation. The results indicate that this programme is effective in helping to meet the basic needs of poor families and informal workers. Students also experienced an increase in solidarity and social awareness. Based on an ABCD-based SWOT analysis, the programme’s main strengths lie in the high level of student participation and strong social capital, whilst its challenges include resource constraints and programme sustainability. Overall, this Community Service Programme (PkM) has successfully strengthened social awareness and affirmed the active role of students in the community.